PERAN ADMINISTRASI PERSONALIA DALAM PENGEMBANGAN PROFESIONALISME GURU DAN TENAGA KEPENDIDIKAN - Agustina, Aulia; Shalshabilla, Siska; Meriana, Sesi; Andriesgo, Johan; Aziranaini, Aziranaini; Afifah, Nur Hadana; Safura, Safura (STKIP Pesisir Selatan, 2025)
The quality of education is highly dependent on the presence and professionalism of teachers and educational staff. This article aims to analyze the role of personnel administration in enhancing the professionalism of educators and educational personnel through a literature review approach. In the context of human resource management within education, personnel administration plays a strategic role that includes planning, recruitment, training, career development, and performance evaluation. The effective implementation of personnel administration can create a supportive work environment, boost motivation and employee performance, and contribute to the achievement of educational goals. The professionalism of teachers and educational staff is defined as the ability to meet the standards of pedagogical, professional, personal, and social competencies as regulated by existing legislation. Moreover, the relationship between personnel administration and human resource development is a crucial factor in improving the competitiveness of educators through continuous training and structured career management. This article also recommends that educational institutions optimize the function of personnel administration as a strategic tool for producing professional and high-quality educators.